Polycystin‐1 modulates RUNX2 activation and osteocalcin gene expression via ERK signalling in a human craniosynostosis cell model. Issue 7 (3rd March 2021) - Katsianou, Maira; Papavassiliou, Kostas A.; Zoi, Ilianna; Gargalionis, Antonios N.; Panagopoulos, Dimitrios; Themistocleous, Marios S.; Piperi, Christina; Papavassiliou, Athanasios G.; Basdra, Efthimia K.
Abstract: Craniosynostosis refers to the premature fusion of one or more cranial sutures leading to skull shape deformities and brain growth restriction. Among the many factors that contribute to abnormal suture fusion, mechanical forces seem to play a major role. Nevertheless, the underlying mechanobiology‐related mechanisms of craniosynostosis still remain unknown. Understanding how aberrant mechanosensation and mechanotransduction drive premature suture fusion will offer important insights into the pathophysiology of craniosynostosis and result in the development of new therapies, which can be used to intervene at an early stage and prevent premature suture fusion. Herein, we provide evidence for the first time on the role of polycystin‐1 (PC1), a key protein in cellular mechanosensitivity, in craniosynostosis, using primary cranial suture cells isolated from patients with trigonocephaly and dolichocephaly, two common types of craniosynostosis. Initially, we showed that PC1 is expressed at the mRNA and protein level in both trigonocephaly and dolichocephaly cranial suture cells. Followingly, by utilizing an antibody against the mechanosensing extracellular N‐terminal domain of PC1, we demonstrated that PC1 regulates runt‐related transcription factor 2 (RUNX2) activation and osteocalcin gene expression via extracellular signal–regulated kinase (ERK) signalling in our human craniosynostosis cell model. Altogether, our study reveals a novel mechanotransduction signalling axis, PC1‐ERK‐RUNX2, which affects osteoblastic differentiation in cranial suture cells from trigonocephaly and dolichocephaly patients.